Morphology and multigene phylogeny unveil Waltergamsia xishuangbannaensis sp. nov. (Bionectriaceae, Hypocreales), associated with Pará rubber (Hevea brasiliensis) from Yunnan Province, China - Liu, Rui-Meng; Xu, Rui-Fang; Elgorban, Abdallah M.; Xu, Jianchu; Dai, Dong-Qin; Suwannarach, Nakarin; Karunarathna, Samantha C.; Tibpromma, Saowaluck (Phytotaxa, 2025)
During a survey of fungi associated with Pará rubber (Hevea brasiliensis) in Xishuangbanna, Yunnan Province, fungal masses that grew on old rubber latex were collected and isolated. Based on DNA sequences of the internal transcribed spacer ribosomal RNA locus (ITS), the nuclear ribosomal large subunit (LSU), partial translation elongation factor 1-alpha (tef1-α), and RNA polymerase II subunit 2 (rpb2) genes, coupled with morphological characteristics, the isolated fungal strains were identified as a novel fungal species, Waltergamsia xishuangbannaensis. A description, illustrations, and phylogenetic analysis results of the new species are presented. In addition, the new species is compared with closely related taxa.